The History of Joint-Stock Companies in the Second Polish Republic as Exemplified by Wspólnota Interesów Górniczo–Hutniczych SA (Mining and Metallurgy Community of Interests Joint Stock Company) - Majewski, Mariusz W. (Studia Historiae Oeconomicae, 2018)
The article focuses on problems related to capital in Katowicka Spółka Akcyjna dla Górnictwa i Hutnictwa SA (Katowice Mining and Metallurgy Joint Stock Company) and Górnośląskie Zjednoczone Huty “Królewska” i “Laura” (Upper Silesian United Metallurgical Plants “Królewska” and “Laura”) in the years 1918–1939. The article examines particular issues of the Upper Silesian industry after the Great War, namely: concentration of foreign capital in the mining and metallurgical industries; great mining and metallurgical enterprises in the periods of both industrial prosperity and crisis; attempts to limit the influence of foreign capital following the introduction of judicial supervision over Katowicka Spółka Akcyjna dla Górnictwa i Hutnictwa SA and Górnośląskie Zjednoczone Huty “Królewska” i “Laura” SA; the emergence of Wspólnota Interesów Górniczo– Hutniczych SA (Mining and Metallurgy Community of Interests Joint Stock Company) in the final years of the Second Polish Republic.